2014
DOI: 10.1056/nejmoa1405858
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of MERS-Coronavirus in Household Contacts

Abstract: The rate of secondary transmission among household contacts of patients with MERS-CoV infection has been approximately 5%. Our data provide insight into the rate of subclinical transmission of MERS-CoV in the home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
375
4
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(413 citation statements)
references
References 21 publications
(30 reference statements)
25
375
4
7
Order By: Relevance
“…The occurrence of large familial clusters of severe cases of MERS is relatively uncommon (16)(17)(18). The secondary attack rate in the family was much higher (23%) than those reported in previous studies (about 5%) (19)(20)(21). Factors that probably contributed to occurrence of many cases in the family were probably related to the crowded living to ensure sustained compliance to IPC guidelines using a scoring method; the audits monitor performance of HCFs, and implementation of immediate corrective actions as deemed necessary (30).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The occurrence of large familial clusters of severe cases of MERS is relatively uncommon (16)(17)(18). The secondary attack rate in the family was much higher (23%) than those reported in previous studies (about 5%) (19)(20)(21). Factors that probably contributed to occurrence of many cases in the family were probably related to the crowded living to ensure sustained compliance to IPC guidelines using a scoring method; the audits monitor performance of HCFs, and implementation of immediate corrective actions as deemed necessary (30).…”
Section: Discussionmentioning
confidence: 90%
“…Increasing public awareness through risk communication is the core activity for reducing or preventing the emergence of primary cases; whereas efficient IPC programmes are required to prevent secondary infections (9,12,19,24,25). The occurrence of secondary cases of MERS in hospitals is an indicator of laxity and complacency in implementing IPC measures or shortage of human resources, equipment, supplies or supervision.…”
Section: The Epidemic Curvementioning
confidence: 99%
“…2 The rate of secondary transmission is low, ranging anywhere from 1-4%. 3,4 However, those individuals who con-tacted the Middle East Respiratory Syndrome coronavirus infection did get significantly ill, with case fatality rates varying from 36 to 70% based on the underlying comorbidities and severity of pneumonia. 2,4,5 As of August 21, 2015, 1,432 laboratory-confirmed cases of infection with Middle East Respiratory Syndrome coronavirus had been reported to the World Health Organization with cases from recent outbreaks in Korea and Saudi Arabia, including at least 507 related deaths, with no complete eradication of the virus in sight.…”
Section: Introductionmentioning
confidence: 99%
“…1 The rate of secondary transmission seems to be low; 2,3 however, those who contract the disease can get significantly sick. Studies have reported that the fatality rates range anywhere from 36% to 70% based on the underlying comorbidities and severity of pneumonia.…”
mentioning
confidence: 99%